SYSTEMATIC BORDER CONTROL ON ROAD BCP – CHALLENGES OF SERVICE ORGANIZATION - Kuprijanova, Jekaterina; Volkova, Jelena; Agafonova, Lidija (Border Security and Management, 2018)
The authors of this article describe the current situation in the service organization of the road border crossing points of the State Border Guard (SBG) of the Republic of Latvia. There are summarized the information based about the legal acts regulating the systematic border control in the international and national legislation and the essence of their execution. There are analysed the use of human resources and possible solutions at the border crossing points and are provided comparative description of the border control points, emphasizing positive and negative features, and also the need for different approaches to service organization by organizing effective systematic border control.